1998
DOI: 10.1046/j.1523-1755.1998.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone improves renal function and fibrosis in the post-obstructed kidney

Abstract: These results demonstrate that PFD can attenuate both renal fibrosis and renal damage in this model, and suggest that PFD can be clinically useful for preventing progressive, irreversible renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
76
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 34 publications
9
76
1
1
Order By: Relevance
“…In our study, there was an improvement in GFR, though with a predominant effect on collagen within the interstitium and tubules, and less so on glomerular lesions. This bears some similarity to recent studies of pirfenidone treatment in fibrotic kidney diseases such as the post-obstructive kidney model (42) and chronic cyclosporine nephrotoxicity (43). In these studies, pirfenidone treatment improved reduced the histologic severity of disease, and reduced collagen content within the kidney.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, there was an improvement in GFR, though with a predominant effect on collagen within the interstitium and tubules, and less so on glomerular lesions. This bears some similarity to recent studies of pirfenidone treatment in fibrotic kidney diseases such as the post-obstructive kidney model (42) and chronic cyclosporine nephrotoxicity (43). In these studies, pirfenidone treatment improved reduced the histologic severity of disease, and reduced collagen content within the kidney.…”
Section: Discussionsupporting
confidence: 78%
“…Recent research has demonstrated that various cytokines and chemokines including TGF-b, TNF-a, and ICAM-1 are involved in renal fibrosis induced by UUO. 27,29,30 Our study also showed that ICAM-1 and TNF-a mRNA expression was upregulated in the UUO group. Furthermore, treatment with RSV markedly decreased these mRNA levels.…”
Section: Discussionsupporting
confidence: 67%
“…26 A previous study has shown that TGF-b levels increased from day 3 after UUO surgery. 27 Similarly, we also found that TGF-b mRNA expression was significantly elevated in the UUO group. However, treatment with RSV significantly decreased TGF-b expression.…”
Section: Discussionsupporting
confidence: 64%
“…Pirfenidone reduces fibrosis and prevents loss of glomerular filtration in animal models of renal disease (9 -14). In the five-sixths nephrectomy rat model of postadaptive FSGS, pirfenidone treatment for 12 wk attenuates the accumulation of glomerular matrix protein, the expression of glomerular TGF-␤, and the loss of glomerular filtration (14,15). Clinical trials that have evaluated safety and efficacy of pirfenidone in various fibrotic diseases have also been encouraging.…”
mentioning
confidence: 99%